2014
DOI: 10.1097/wnr.0000000000000216
|View full text |Cite
|
Sign up to set email alerts
|

Mutational characterization of ATP7B gene in 103 Wilson’s disease patients from Southern China

Abstract: Wilson's disease (WD) is an autosomal recessive inheritance disorder of copper metabolism due to mutations in the ATP7B gene. The distribution of ATP7B gene mutations is diverse in different population. This study aimed to examine the genotypes of the ATP7B mutant alleles in WD patients from Southern China. Genomic DNA was extracted from 103 WD patients and 60 healthy patients. Mutations were screened and detected by DNA sequencing. A total of 51 different ATP7B mutations were identified in WD patients, includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
29
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 19 publications
3
29
1
Order By: Relevance
“…Alterations in the gene, which is responsible for the synthesis of protein P-type ATPase (ATP7B), lead to pathological copper accumulation, especially in the liver and the brain [2]. Copper accumulation usually causes severe clinical manifestations, including liver failure, hepatitis [3], cirrhosis [4], premature death [5], and motor [6], emotion, cognitive impairments [7].…”
Section: Introductionmentioning
confidence: 99%
“…Alterations in the gene, which is responsible for the synthesis of protein P-type ATPase (ATP7B), lead to pathological copper accumulation, especially in the liver and the brain [2]. Copper accumulation usually causes severe clinical manifestations, including liver failure, hepatitis [3], cirrhosis [4], premature death [5], and motor [6], emotion, cognitive impairments [7].…”
Section: Introductionmentioning
confidence: 99%
“…Mutation hotspots in ATP7B vary by geographic region, with a higher prevalence of specific variants reported in certain populations. The predominant variants in the Chinese population include c.2333G>T (p.Arg778Leu), c.2975C>T (p.Pro992Leu), c.3443T>C (p.Ile1148Thr), and c.2804C>T (p.Thr935Met) (Gu et al, ; Wang et al, ; Wei et al, ). In our study, the most frequently observed DVs were c.2333G>T, c.2304dupC, c.2621C>T, c.588C>A, c.1708‐5T>G, c.2827G>A, c.2975C>T, c.3053C>T, c.3646G>A, c.A3809A>G, and c.4114C>T. The one silent variant was c.2310C>G. The two uncertain variants (DVs or NDVs) were c.3316G>A and c.3443T>C.…”
Section: Discussionmentioning
confidence: 99%
“…Mutation hotspots in ATP7B vary by geographic region, with a higher prevalence of specific variants reported in certain populations. The predominant variants in the Chinese population include c.2333G>T (p.Arg778Leu), c.2975C>T (p.Pro992Leu), c.3443T>C (p.Ile1148Thr), and c.2804C>T (p.Thr935Met) (Gu et al, 2003;Wang et al, 2011;Wei et al, 2014). In our study, the most frequently observed In our study, we found six novel variants, of which two were synonymous mutations (c.1875T>A and c.3243G>A) and four were possible DVs (c.2306T>C, c.3028A>G, c.3437_3438 delTG, and c.3903+5G>A).…”
Section: Discussionmentioning
confidence: 99%
“…Among these mutations, p.Arg778Leu (c.2333G>T) has been identified as the most common. Both p.Pro992Leu (c.2975C>T) and p.Val1106Ile (c.3317G>A) are also relatively frequent mutations in WD, and also play important roles in the detection of WD …”
Section: Introductionmentioning
confidence: 99%
“…Both p.Pro992Leu (c.2975C>T) and p.Val1106Ile (c.3317G>A) are also relatively frequent mutations in WD, and also play important roles in the detection of WD. [5][6][7] Various approaches have been described for the detection of ATP7B gene mutations, such as multi-allele genotyping, genotyping microarray, and Sanger sequencing, but the clinical uses of these approaches are limited. 8,9 Recently, high-resolution melting (HRM) analysis was developed as a closed-tube technology for genotyping DNA variants and mutation screening, with advantages over other techniques such as its high-throughput, rapid, and nondestructive nature.…”
mentioning
confidence: 99%